2002
DOI: 10.1159/000047742
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Microemboli in 33 Patients with Intracranial Arterial Stenosis

Abstract: Background: Intracranial arterial stenosis is a rare cause of stroke in Caucasians. Detection of clinically silent circulating microemboli by transcranial Doppler sonography is now widely investigated in patients with carotid artery disease in the hope to identify patients at increased risk for stroke. Methods: In 33 patients with intracranial internal carotid (n = 12), middle cerebral (n = 18), posterior cerebral (n = 2), or basilar artery stenosis (n = 1), we performed a 1-hour microembolus detection downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
2
21
1
1
Order By: Relevance
“…This is supported by the observations of Droste et al, 20 who reported that microemboli in intracranial stenosis were found only in symptomatic patients with severe stenosis.…”
Section: Discussionsupporting
confidence: 81%
“…This is supported by the observations of Droste et al, 20 who reported that microemboli in intracranial stenosis were found only in symptomatic patients with severe stenosis.…”
Section: Discussionsupporting
confidence: 81%
“…21 Droste et al reported that MES were mainly observed in patients with recent symptomatic intracranial atherosclerosis and severe stenosis only. 30 The short delay between symptoms and TCD may explain the relatively high prevalence of MES in the present study.…”
Section: Discussion Prevalence Of Mesmentioning
confidence: 57%
“…The clinical impact of artery-to-artery embolism may increase in the presence of hemodynamic compromise that exists in patients with steno-occlusive lesions and insufficient collateral blood supply. Under these conditions, impaired microemboli wash-out due to hemodynamic compromise may augment the risk for the occurrence of cerebral infarctions as shown in patients with middle cerebral artery stenosis or carotid artery occlusion [7, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%